Structure and collective dynamics of liquid sodium - Patel, V.N.; Thakor, P.B.; Thakore, B.Y.; Gajjar, P.N.; Jani, A.R. (Condensed Matter Physics, 2006)
The temperature variation of the longitudinal and transverse phonon frequencies of liquid sodium is investigated using the approach by Hubbard Beeby. The molecular dynamics simulation is used to generate the pair correlation function of liquid sodium at various temperatures viz. T = 378 K, 473 K, 573 K, and 723 K, with 672 particles. To describe the electron-ion interaction our own model potential is employed along with a recent local field correction function due to Sarkar et al. To evaluate the parameter of the potential the zero pressure condition has been applied. The present results of g(r) are in good agreement with available experimental findings. The computed g(r) are used to investigate the temperature variation of the collective dynamics of liquid sodium. The amplitudes of the peaks of the longitudinal and transverse frequencies are suppressed while the width of the propagation gap for the transverse sound waves decreases with an increase in temperature. The computed longitudinal and transverse sound velocities at these temperatures are found to be encouraging.